2020
DOI: 10.1177/1362361320932437
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between intolerance of uncertainty and anxiety in autism: A systematic literature review and meta-analysis

Abstract: The association between intolerance of uncertainty and anxiety has proved robust in neurotypical populations and has led to effective interventions targeting intolerance of uncertainty. The aim of this systematic review and meta-analysis was to investigate this association in autistic people, given the high prevalence of anxiety in this population and the limited effectiveness of therapies used currently to treat anxiety in autism. A protocol was published on the Prospero database (CRD42019125315), and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 63 publications
(94 reference statements)
6
63
0
6
Order By: Relevance
“…Scores range from 1-60, with higher scores indicating higher levels of intolerance of uncertainty. However, this scale although widely used in studies of autistic people, has not yet been validated in this group [37]. In the current study, Cronbach's alpha showed excellent internal consistency for the IUS-12 total scale α=.87.…”
Section: Intolerance Of Uncertainty Scale -Short Formmentioning
confidence: 50%
“…Scores range from 1-60, with higher scores indicating higher levels of intolerance of uncertainty. However, this scale although widely used in studies of autistic people, has not yet been validated in this group [37]. In the current study, Cronbach's alpha showed excellent internal consistency for the IUS-12 total scale α=.87.…”
Section: Intolerance Of Uncertainty Scale -Short Formmentioning
confidence: 50%
“…Hwang et al, 2020;Vasa et al, 2018). IU has been closely linked to anxiety in autistic people (Jenkinson et al, 2020), and also relates to core features of autism, including social difficulties, sensory sensitivities, insistence on sameness and repetitive behaviours (e.g. Hwang et al, 2020;Vasa et al, 2018;Wigham et al, 2015).…”
Section: Intolerance Of Uncertaintymentioning
confidence: 99%
“…Originally conceptualised in relation to generalised anxiety disorder in neurotypical adulthood, IU has emerged as an important process mechanism in both the development and maintenance of anxiety in autistic children and adults. The recent meta‐analysis by Jenkinson and colleagues (Jenkinson, Milne, & Thompson, 2020) reaffirms the importance of IU as a treatment target in autism, as it is in neurotypical samples. However, recent conceptual models of the relationship between IU and anxiety in neurotypical people have suggested that a traditional therapeutic focus on mitigating fear responses in anxious individuals may be missing a more pertinent difficulty in recognising safety cues (see e.g.…”
mentioning
confidence: 93%